Classification and Interpretation for 11 FBN1 Variants Responsible for Marfan Syndrome and Pre-implantation Genetic Testing (PGT) for Two Families Successfully Blocked Transmission of the Pathogenic Mutations - Chen, Songchang; Fei, Hongjun; Zhang, Junyun; Chen, Yiyao; Huang, Hefeng; Lu, Daru; Xu, Chenming (Frontiers in Molecular Biosciences, 2021)
Background: The lifespan of Marfan Syndrome (MFS) patients is shortened, especially in patients without early diagnostics, preventive treatment, and elective surgery. Clinically, MFS diagnosis is mainly dependent on phenotypes, but for children, sporadic cases, or suspicious MFS patients, molecular genetic testing, and mainly FBN1 mutation screening, plays a significant role in the diagnosis of MFS. PGT-M gives couples that had a family history of monogenic disorders the opportunity to avoid the occurrence of MFS. Methods: In this study, 11 families with MFS were recruited and complete clinical features were collected. Variants were classified and interpreted through pedigree analysis according to guidelines. Two families chose to undergo PGT-M; 16 blastocysts were biopsied and amplified. Haplotype analysis was performed to deduce the embryo’s genotype by using single nucleotide polymorphisms (SNPs) identified in each sample. Results: We identified 11 potential disease-causing FBN1 variants, six of which are novel. All variants were assessed with prediction tools to assess mutation pathogenicity, population databases to evaluate population allele frequency, literature databases to identify whether the variant had been reported in MFS patients, and multiple sequence alignment to carry out conservative analysis. Finally, nine variants were classified as likely pathogenic/pathogenic variants. Among 11 variants, eight variants were missense, and seven of them were located in the Ca-binding EGF-like motifs, moreover, half of them substituted conserved Cysteine residues. We also identified a splice site variant, a frameshift variant, and a synonymous variant. There are two variants that are de novo variants. PGT-M helped two MFS families give birth to a healthy baby not carrying the FBN1 mutation. Conclusions: In the present study, the FBN1 mutation spectrum was enriched, and may help further elucidate the pathogenesis, benefiting clinical diagnosis and management of MFS. We make use of a reliable PGT-M method for the successful birth of healthy babies to two MFS families.